Crowd of people at celebration of U.S. naval victories during the Spanish-American War, Dawson, ca. 1898 - Nowell, Frank H., 1864-1950 (1898)
Caption on image: Celebration at Dawson of U.S. Naval Victories. Photo by F.H. Nowell, 1992. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number